Beyond the rural-urban divide cross-continental perspectives on the differentiated countryside and its regulation - Andersson, Kjell (Emerald Group Pub Ltd., 2009)
The rural-urban dichotomy is one of the most influential figures of thought in history, laying the foundation for academic disciplines such as rural and urban sociology. The dichotomy rests on the assumption that rural and urban areas differ fundamentally. By the mid-twentieth century, scholars had observed that many rural areas displayed a blend of rural and urban features. Since then, counterurbanisation, urban sprawl and ever-increasing flows of people, goods and ideas between rural and urban areas have blurred the distinctions even further. Attempts to create new rural-urban classification systems, whether based on factors such as population size, density or distances, have largely failed. Clearly, new classification systems must use the meaning of observed changes in rural-urban systems as their point of departure rather than simple measurements of these changes. These meanings can, despite the interdependencies of our global world, be explored only in their political, cultural and economic settings.